The Multimodal Evocation of Minds in Audio Drama. Issue 3 (December 2019) - Bernaerts, Lars
Abstract : This article discusses the construction of fictional minds in audio drama. Drawing upon social semiotics, cognitive narratology, and the narratology of audio drama, it starts from the premise that a character's consciousness in radio plays is shaped by the conventions, constraints, and affordances of the medium. This means that the semiotic modes of the radio play are exploited in a particular way to give listeners the impression that they are accessing a character's mind, e.g. through a voice's pitch or the verbal rendering of thoughts. In a dynamics of remediation, audio drama conventionally adopts narrative strategies associated with drama (e.g., soliloquy) as well as novelistic (e.g., thought report by a heterodiegetic narrator) and cinematic procedures (e.g., extradiegetic music as an accompaniment to characters' emotions) to evoke minds. Three adaptations will serve to illustrate this dynamics: Madame Bovary (PBS, 1986), Oeroeg (2009) and The Divine Comedy (BBC, 2014). By taking imported conventions into account alongside the audiophonic deployment of voice, music, sound, silence, and words, the article aims to further our understanding of minds in audio drama – which is relatively unknown territory in narratology – and contribute to the debate on fictional minds in cognitive and transmedial narratology.